Operative Dictations in General and Vascular Surgery - Hoballah, Jamal J.; Scott-Conner, Carol E. H.; Chong, Hui Sen (Springer International Publishing : Imprint: Springer, 2017)
This text is a fully updated and revised third edition of a highly successful text. The format of this text is unique and has been very successful. A total of 286 short chapters organized into 24 Sections provide operative dictation templates for all of the common and the vast majority of the uncommon and even rare operations performed by general and vascular surgeons. Each chapter also provides a succinct synopsis of the operation through bullet-ed lists which include Indications, Essential Steps, Note these Variations, and Complications. The book thus serves two purposes: these operative dictation templates can be used verbatim when dictating the operative note for a procedure; and the book provides ready reference to the trainee going into the operating room to do the procedure for the first time, or to someone preparing for their Board examinations. Space for notes allows surgeons to personalize the book and turn it into a resource unique to their situation. Fully updated and expanded, Operative Dictations in General and Vascular Surgery, Third Edition includes significant additions that include flexible endoscopic procedures (now recognized as a core part of general surgery training and practice), single incision laparoscopic cholecystectomy, and robotic approaches to the rectum. The endovascular procedures have been significantly expanded, as have the approaches to venous disease and to A-V fistula creation. Operative Dictations in General and Vascular Surgery, Third Edition is intended for practicing surgeons, who may modify each template to reflect their own individual practice. It also serves as a concise reminder of essential steps in those operations that may be only rarely performed.
Keywords: Medicine.; Abdominal surgery.; Surgery.; Minimally invasive surgery.; Thoracic surgery.; Vascular surgery.; elektronické knihy; electronic books